2017
DOI: 10.1038/s41598-017-13152-2
|View full text |Cite
|
Sign up to set email alerts
|

Conformations and molecular interactions of poly-γ-glutamic acid as a soluble microbial product in aqueous solutions

Abstract: Soluble microbial products (SMPs) are of significant concern in the natural environment and in engineered systems. In this work, poly-γ-glutamic acid (γ-PGA), which is predominantly produced by Bacillus sp., was investigated in terms of pH-induced conformational changes and molecular interactions in aqueous solutions; accordingly, its sedimentation coefficient distribution and viscosity were also elucidated. Experimental results indicate that pH has a significant impact on the structure and molecular interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 43 publications
1
28
0
Order By: Relevance
“…There are few reports on the antimicrobial functions of pure γPGA. Although it is reported that higher molecular weight of polymer may diffuse slowly, the factors that are considered for antimicrobial activity are surface charge, hydrophobicity, hydrophilicity, and intramolecular hydrogen bonding (Khalil et al, 2017; Wang et al, 2017), and these differ between producing strains.…”
Section: Resultsmentioning
confidence: 99%
“…There are few reports on the antimicrobial functions of pure γPGA. Although it is reported that higher molecular weight of polymer may diffuse slowly, the factors that are considered for antimicrobial activity are surface charge, hydrophobicity, hydrophilicity, and intramolecular hydrogen bonding (Khalil et al, 2017; Wang et al, 2017), and these differ between producing strains.…”
Section: Resultsmentioning
confidence: 99%
“…The p K a of γ-PGA was determined to be 4.86 [21] in our previous study and Fig 1(A) illustrates the effect of pH on γ-PGA species. The acid form γ-PGA-H rapidly ionized to form the mono-anionic γ-PGA - specie as the pH increased from pH 3.0 to 7.0.…”
Section: Resultsmentioning
confidence: 99%
“…The purity and glutamic acid content of γ-PGA were determined by amino acid analysis using thin layer chromatography (TLC) and colorimetric analysis after hydrolysis as described by Wang et al [21]. Metal ions were analyzed using an inductively coupled plasma mass spectrometer (ICP-MS, 7700X, Agilent Inc., USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations